'This is my vocation; is it worth it?' Why do core medical trainees break from training?. (2020) - Roycroft, Matthew; Abad-Madroñero, Juan; Cochrane, Charlotte; Poots, Alan; Novak, Mariann; Tallett, Amy; Burger, Sarah-Ann; FitzPatrick, Michael
No abstract available